Impregnating ultrafine FeS2 nanoparticles within hierarchical carbon tubes for advanced potassium-ion batteries. Issue 4 (13th January 2023) - Zhang, Zhuangzhuang; Qiao, Yaru; Deng, Qinghua; Jia, Mengmin; Liu, Dai-Huo; Dai, Dongmei; Li, Bao
Abstract : FeS2 -C@CTs is synthesized by a template-assisted vulcanization strategy, exhibiting high reversible capacity, excellent rate capability and stable cycling performance toward potassium-ion batteries. Abstract : Transition-metal sulfides (TMSs) with high theoretical capacity and economical suitability are attractive anode materials for potassium-ion batteries (PIBs). However, the inherent low conductivity, tardy K + diffusion kinetics, and huge volume change of TMSs pose a lot of challenges, impeding their practical application in PIBs. Herein, a simple template-assisted vulcanization strategy is presented for impregnating ultrasmall FeS2 nanoparticles within flexible carbon nanowires wrapped with robust amorphous carbon tubes (denoted as FeS2 -C@CTs), resolving the abovementioned issues and improving the electrochemical performance of PIBs. Specifically, such a crafted FeS2 -C@CT-based anode delivers a high reversible capacity of 524 mA h g −1 at 50 mA g −1, an intriguing rate capability of 208 mA h g −1 at 10 A g −1, and a decent cycling stability of 167 mA h g −1 at 10 A g −1 after 1000 cycles. More importantly, a full cell (K0.6 CoO2 //FeS2 -C@CTs) also delivers an enhanced potassium storage performance, showing a high rate capacity of 123 mA h g −1 at 1 A g −1 and a long cycle life with a capacity retention rate of 87.6% after 200 cycles.